Mechanical Response of HPFRCC in Tension and Compression at High Strain Rate and High Temperature - CADONI, E.; BRAGOV, A. M.; CAVERZAN, A.; DI PRISCO, M.; KONSTANTINOV, A.; LOMUNOV, A. (Engineering Transactions, 2010)
The mechanical response of High Performance Fibre-Reinforced Cementitious Composite (HPFRCC) has been analyzed at high strain rates and high temperature. Two experimental devices have been used for compression and tension tests: the traditional Split Hopkinson Pressure Bar for compression and the JRC-Split Hopkinson Tension Bar for tension. The HPFRCC was thermally damaged at 3 temperatures (200°C, 400°C and 600°C) in order to analyze the dynamic behaviour of this material when explosions and fires took place in a tunnel. Results show that significant peak strength increases both in tension and in compression. The post-peak strength in tension depends on the thermal damage of the material. Its strain- rate sensitivity and thermal damage have been illustrated by means of a Dynamic Increase Factor. These results show that it is necessary to implement new expression of the DIF for the HPFRCC, therefore more and more accurate and experimental studies using Kolsky–Hopkinson Bar methods are needful.